Diversity-oriented functionalization of 2-pyridones and uracils - Yong Shang (Nature Portfolio, 2021)
Diversity-oriented synthesis of 2-pyridone and uracil derivatives is in urgent need in medicinal chemistry as they are useful pharmacophores. Here the authors show that palladium/norbornene cooperative catalysis enabled dual-functionalization of iodinated 2- pyridones and uracils.